Palestine at the end of the state-building process: Technical achievements, political failures. Issue 4 (2nd October 2018) - Persson, Anders
Abstract: More than two decades of Palestinian state-building have produced neither peace nor a state. In fact, the Palestinians are seemingly further away from statehood today than at any point since the state-building process began in the mid-90s, despite the fact that the West Bank's institutions now perform, according to the UN, the EU, the World Bank and IMF, above the threshold for what is expected of a state. In this situation – with the Palestinians technically ready for statehood and large parts of Europe and the U.S. not politically ready to recognize Palestine – it is unclear what strategic objectives the internationally supported state-building process now can achieve in the Palestinian territories, except for upholding the status quo.